Shaking Table Test of a Full-Scale RC Frame Structure with an Indoor Gas Piping System - Dezhang Sun; Endong Guo; Houli Wu; Zhibin Liu; Chenxi Mao; Haoyu Zhang; Xun Sun (Advances in Civil Engineering)
To investigate the seismic behavior of a two-story RC frame structure with an indoor gas piping system, a shaking table test was performed and the data obtained from the shaking table test were analyzed in this paper. The detailing of the structural elements was compliant with the Chinese seismic design code, whereas minor modifications were applied to the pipe materials and joint arrangements. In the test, three kinds of pipe materials (galvanized steel, thin-walled stainless steel, and polyethylene) combined with three types of joint arrangements were selected. The filling materials of the joint were epoxy resin, batched jute, and asbestos cement. A series of full-scale shake table tests were performed by gradually increasing the three ground motions for reaching to the near collapse limit state. The dynamic characteristics and the responses of the model were investigated via analyzing shaking table test data and the observed damage. The test results also indicated that different joint arrangements had a different impact on the dynamic response of the pipes when subjected to strong ground motions. The peak acceleration of metal pipes with a rigid joint was higher than that of flexible ones, and the peak acceleration of plastic pipes with flexible joint connection was higher than that of rigid ones.